Organ-based tube current modulation in chest CT. A comparison of three vendors. Issue 1 (February 2021) - Mussmann, B.R.; Mørup, S.D.; Skov, P.M.; Foley, S.; Brenøe, A.S.; Eldahl, F.; Jørgensen, G.M.; Precht, H.
Abstract: Introduction: Organ-based tube current modulation (OBTCM) is designed for anterior dose reduction in Computed Tomography (CT). The purpose was to assess dose reduction capability in chest CT using three organ dose modulation systems at different kVp settings. Furthermore, noise, diagnostic image quality and tumour detection was assessed. Methods: A Lungman phantom was scanned with and without OBTCM at 80–135/140 kVp using three CT scanners; Canon Aquillion Prime, GE Revolution CT and Siemens Somatom Flash. Thermo-luminescent dosimeters were attached to the phantom surface and all scans were repeated five times. Image noise was measured in three ROIs at the level of the carina. Three observers visually scored the images using a fivestep scale. A Wilcoxon Signed-Rank test was used for statistical analysis of differences. Results: Using the GE revolution CT scanner, dose reductions between 1.10 mSv (12%) and 1.56 mSv (24%) (p < 0.01) were found in the anterior segment and no differences posteriorly and laterally. Total dose reductions between 0.64 (8%) and 0.91 mSv (13%) were found across kVp levels (p < 0.00001). Maximum noise increase with OBTCM was 0.8 HU. With the Canon system, anterior dose reductions of 6–10% and total dose reduction of 0.74–0.76 mSv across kVp levels (p < 0.001) were found with a maximum noise increase of 1.1 HU. For the Siemens system, dose increased by 22–51% anteriorly; except at 100 kVp where no dose difference was found. Noise decreased by 1 to 1.5 HU. Conclusion: Organ based tube current modulation is capable of anterior and total dose reduction with minimal loss of image quality in vendors that do not increase posterior dose. Implications for practice: This research highlights the importance of being familiar with dose reduction technologies.